Optimisation of honey-based hydrogel formulations using response surface modeling - Ab. Hadi, Hazrina; Abdul Jalil, Mohd Azri; Awadh, Ammar Ihsan JawaD (2016)
Response surface modeling (RSM) is used by scientists to relate the factors and response variables by using a design matrix that eventually produce optimal formulations. Hence, the objective of this paper is to optimize the honey-based hydrogel formulations by using RSM. From the two level factorial design result, the optimization test were conducted by using central composite design (CCD) from design experiment software version 8 (DOE 8, Minnesota, USA) to obtain the optimized formulation and control formulation. For hydrogel mixture, polyvinyl alcohol (PVA) and polyethylene glycol (PEG) were used. From the formulation lists, three response (swelling ratio, water vapor transmission and gel fraction) were chosen to study the influence of the factors selected towards the formulations. For the swelling ratio response, only honey concentration shows a significant. Honey concentration and number of cycles showed a significant effect towards the response on water vapor transmission rate. Honey concentration has the most significant effect on the gel fraction percentage. As a conclusion, from this optimization test, the formulation with honey and minimal number of cycles show a good reaction towards the selected response.